PEMBENTUKAN AWAL GENERASI MUKMIN DALAM AL-QUR’AN HADITS DAN IMPLIKASINYA PADA SISWA SEKOLAH DASAR ISLAM TERPADU IMAM ASY-SYAFII PEKANBARU - Wismanto Wismanto Wismanto (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2021)
Problems are often faced and witnessed by observer; parents to their children, society to children and adolescents in their environment, teachers to their students, KPK against government and private employees; is a matter of moral decadence which has reached its lowest level, even lower than animals. Therefore it is necessary to do research what causes it and what kind of education which can fix it. Based on the above thoughts, the study of formation pattern on Muchmin Generation in accordance with Prophet Muhammad thoughts becomes something urgent for the improvement of children morals and character in this nation. The methodology of this research is kualitatif Research. Reseacrh focus is to make generation formative study from guaranteed sources of Islamic science, namely Qur'an and Hadith. The results of this study indicate that students who are given Islamic education based on Qur'an and Sunnah can form a good generation (muchmin), this is indicated by visible understanding of straight monotheism, keeping five daily prayers and coupled with habit of memorizing Al Qur'an 15 minutes before prayer, children also go to mosque 15 minutes before the call to prayer (adzan) is sounded boys keep their distance from girls and seem already know that they are not mahram but women who also need to be respected and raised in glory, besides that these students are also accustomed to remembrance and prayers from Qur'an and Sunnah. Keywords: Formation, Muchmin Generation, Al-Qur'an, Hadiths